Immune response in IGF-1 and growth parameters among infected children - Ardianah, Eva; Widjaja, Nur Aisiyah; Indriani, Diah; Melaniani, Soenarnatalina; Kuntoro; Wibowo, Arief; Notobroto, Hari Basuki; Purnomo, Windhu; Indawati, Rachmah; Saputro, Sigit Ari; Santoso, Febrina Mustika; Puspitasari, Ria; Pebriaini, Prisma Andita; Nurfidaus, Yasmine; Irawan, Roedi; Hidayat, Boerhan; Hidayati, Siti Nurul; Hanindita, Meta Herdiana (Universitas Gadjah Mada, 2025)
Purpose: Infections in children can affect weight gain and linear growth by influencing metabolism and nutrition. Chronic inflammation results in growth failure mediated by pro-inflammatory cytokines and poor nutritional intake, which affects the GH/IGF-1 axis. This study aimed to investigate the impact of the inflammatory response on children's anthropometry, particularly HAZ, and the role of IGF-1. Methods: An observational study with a cross-sectional design was conducted from September 2021 to July 2022. The study involved children diagnosed with infections. The subjects had undergone a physical and laboratory investigation, which included a thorax photo, urine culture, Mantoux test, and complete blood test in a hospital setting. A complete medical history was obtained from the pediatrician. Results: The prevalence of undernutrition was 37.33%; the prevalence of underweight/severely underweight, stunted/severely stunted, and wasted/severely wasted was 25.33%, 30.66%, and 14.67% respectively. Stunted/severely stunted was more prevalent in subjects under 2 years old, compared to subjects more than 2 years old (22/41 vs. 7/34, p=0.014). SEM analysis revealed that the inflammatory response affected IGF-1 levels (r=0.850, p=0.000), while IGF-1 affected body composition (r=0.245, p=0.025), and then affected HAZ (r=1.000, p=0.000). The effect of IGF-1 on HAZ appears to be indirect, acting through body composition. Parental height has a weak, albeit significant, effect on body composition (r=0.101, p=0.025) and HAZ (r=0.192, p=0.040). Univariate analysis revealed strong correlations between IL-6 and IL-10 and IGF-1 (r=0.870, p=0.000 and 0.876, p=0.000, respectively). In contrast, parental height showed a correlation with HAZ/LAZ (r=0.319, p=0.000). Maternal height was correlated positively with WAZ (r=0.320, p=0.044). Conclusion: The prevalence of stunting among children under two years of age indicates that early childhood constitutes a critical period for intervention in growth and development. Inflammatory response has been demonstrated to influence IGF-1 levels in children. The role of IGF-1 on HAZ was mediated by body composition.